2004
DOI: 10.1111/j.1540-5826.2004.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended Test Time and postsecondary Students with Learning Disabilities: A Model for Decision Making

Abstract: The most frequently requested accommodation among students with learning disabilities (LD) in postsecondary settings is extended test time. The frequency with which this accommodation is requested and granted compels disability service providers to become knowledgeable about the factors that influence the need for, and appropriateness of, the accommodation. Moreover, the synthesis of these factors becomes the basis for determining if the accommodation is reasonable under federal law. The purpose of this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 57 publications
(68 reference statements)
0
45
0
Order By: Relevance
“…The most frequently requested accommodation among students with learning disabilities in post-secondary settings is extended test time (Ofiesh, Hughes, & Scott, 2004). With the increasing numbers of students registered for this accommodation, at peak periods such as mid-terms disability resource centres are hard pressed to locate sufficient physical space, let alone hire the necessary clerical staff and invigilators to meet the demand.…”
Section: Set Shorter Examsmentioning
confidence: 99%
“…The most frequently requested accommodation among students with learning disabilities in post-secondary settings is extended test time (Ofiesh, Hughes, & Scott, 2004). With the increasing numbers of students registered for this accommodation, at peak periods such as mid-terms disability resource centres are hard pressed to locate sufficient physical space, let alone hire the necessary clerical staff and invigilators to meet the demand.…”
Section: Set Shorter Examsmentioning
confidence: 99%
“…Even in noncompetitive situations, giving additional time can artificially inflate scores, overestimating students’ skill levels, and keeping a test from measuring how fluent and automatic students’ skills are (Phillips, 2011). Scholars have suggested that diagnostic test data be used to estimate how much extended time a student with a disability condition should be given on real-world exams (Ofiesh, Hughes, & Scott, 2004), but no clear guidelines have been developed for translating specific diagnostic test scores into precise amounts of needed additional time. This is another reason that it is important to understand the determinants of test completion time.…”
mentioning
confidence: 99%
“…Using the psychoeducational evaluation, the people responsible for making recommendations for accommodations look for specific indicators to evaluate the request. The parts of the Americans With Disabilities Act of 1990 and Section 504 of the Rehabilitation Act which have been most influential in the design of this process have been requirements for evidence that a disabling condition: (a) exists (e.g., as opposed to evidence of special education services without a noted disabling condition), (b) currently impacts a major life activity, and (c) clearly delineates the functional limitations (Ofiesh, Hughes, & Scott, 2004). These requirements also are applied in institutions of higher education as well as in national testing programs that administer high-stakes exams such as the SAT, GRE, and MCAT.…”
Section: Issues Related To Transition To Postsecondary Settingsmentioning
confidence: 99%